Pre-magnesium pre-lithium silica negative electrode material and preparation method and application thereof
Through the pre-magnesium and pre-lithium treatment method, the rigidity and structural stability of the silicon oxygen negative electrode material are enhanced, the volume expansion and capacity attenuation problems are solved, and the performance and life of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202411366903.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-23
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The silicon oxygen negative electrode material undergoes severe volume expansion during Li+ deintercalation/insertion, resulting in mechanical crushing and reconstruction or shedding of SEI film, causing rapid attenuation of battery capacity, limiting the application of lithium-ion batteries.
Premagnesium prelithium treatment method is adopted to generate magnesium silicate and lithium silicate by reacting with elemental magnesium and lithium hydride, which enhances the rigidity and structural stability of the material, inhibits volume expansion, and participates in battery charging and discharging reactions, and improves battery efficiency.
It effectively suppresses the volume expansion of the silicon oxygen negative electrode material, maintains the electrode structure, improves the capacity retention rate and the first charge and discharge efficiency of the battery, and extends the battery life.
Smart Images

Figure CN119324220A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and more specifically, to a pre-magnesium pre-lithium silicon oxide negative electrode material and a preparation method and application thereof. Background Art
[0002] Rechargeable lithium-ion batteries are considered to be one of the most promising energy storage devices due to their high energy density, long cycle life, and good environmental compatibility. With the rapid development of electric vehicles and smart grids, people have put forward higher energy density requirements. However, the relatively low theoretical capacity of traditional graphite anodes (372mAh / g) has hindered the widespread application of rechargeable lithium-ion batteries, so it is necessary to find potential alternatives to lithium-ion battery anode materials. Among a series of potential alternatives to lithium-ion battery anode materials, silicon has a suitable working potential for lithium storage (0.4V vs Li / Li + ) and ultra-high theoretical capacity (3579 mAh / g at room temperature 25°C) have attracted much attention. + During the deintercalation / insertion process, the silicon-oxygen negative electrode material will undergo severe volume expansion, causing the silicon-oxygen negative electrode material to be mechanically crushed, thereby causing the active substances and solid electrolyte interface film (SEI) to reconstruct or fall off from the silicon-oxygen negative electrode material, destroying the electrode structure, causing rapid attenuation of the battery capacity, and significantly reducing the capacity retention rate of the silicon-oxygen negative electrode material.
[0003] Therefore, it is of great significance to develop a method for preparing pre-magnesium and pre-lithium silicon-oxygen negative electrode materials that can improve the capacity retention rate of silicon-oxygen negative electrode materials. Summary of the invention
[0004] The purpose of the present invention is to solve the deficiencies of the prior art and to provide a pre-magnesium pre-lithium silicon oxide negative electrode material and a preparation method and application thereof.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides a method for preparing a pre-magnesium pre-lithium silicon oxide negative electrode material, the preparation method comprising the following steps:
[0007] A1. Pre-magnesium treatment: mixing silicon-oxygen material and elemental magnesium, calcining to obtain pre-magnesium silicon-oxygen material;
[0008] A2. Pre-lithium treatment: Mix the pre-magnesium silicon oxide material with lithium hydride and calcine to obtain the pre-magnesium pre-lithium silicon oxide negative electrode material;
[0009] and / or
[0010] B1. Pre-lithium treatment: mixing silicon oxygen material with lithium hydride, calcining to obtain a pre-lithium silicon oxygen material;
[0011] B2. Pre-magnesium treatment: mixing the pre-lithium silicon-oxygen material with elemental magnesium and calcining to obtain the pre-magnesium pre-lithium silicon-oxygen negative electrode material;
[0012] The mass ratio of the silicon oxide material to elemental magnesium is 10:(0.2-1); the mass ratio of the silicon oxide material to lithium hydride is 10:(0.1-0.8).
[0013] The method for preparing the pre-magnesium pre-lithium silicon-oxygen negative electrode material of the present invention can increase the rigidity and structural stability of the silicon-oxygen negative electrode material prepared by using the pre-magnesium pre-lithium silicon-oxygen negative electrode material, and inhibit the silicon-oxygen negative electrode material from being heated in the presence of Li + Volume expansion occurs during the process of deintercalation / insertion, which reduces or prevents the reconstruction or detachment of active substances and solid electrolyte interface membrane (SEI) from the silicon-oxygen negative electrode material, maintains the electrode structure, and improves the capacity retention rate of the silicon-oxygen negative electrode material. In addition, elemental magnesium and lithium hydride will also react with silicon-oxygen materials to form magnesium silicate (MgSiO3) and lithium silicate (Li2SiO3), thereby participating in the battery's charge and discharge reaction, improving the battery's initial charge and discharge efficiency, and preventing the battery's charge and discharge capacity from dropping significantly in multiple cycles, thereby improving the capacity retention rate of the silicon-oxygen negative electrode material.
[0014] In the present invention, if the mass ratio of silicon oxide material to elemental magnesium and the mass ratio of silicon oxide material to lithium hydride are too low (i.e., the amount of elemental magnesium and lithium hydride is too much), magnesium and lithium will participate in the formation of more other types of impurity silicates, such as Mg2SiO4 and Li4SiO4, etc., which will continuously consume lithium during the battery cycle and cannot be precipitated, resulting in the inability to improve the charge and discharge efficiency of the battery, and the continuous reduction of the charge and discharge capacity, which affects the life of the silicon oxide negative electrode material and greatly reduces the capacity retention rate of the silicon oxide negative electrode material prepared using the pre-magnesium pre-lithium silicon oxide negative electrode material; if it is too high (i.e., the amount of elemental magnesium and lithium hydride is too low), it is impossible to effectively increase the rigidity and structural stability of the silicon oxide negative electrode material prepared using the pre-magnesium pre-lithium silicon oxide negative electrode material, and it is impossible to inhibit the silicon oxide negative electrode material from being stored in Li + Volume expansion occurs during the deintercalation / insertion process, which ultimately leads to a significant decrease in the capacity retention rate of the silicon-oxygen negative electrode material.
[0015] The reason why the present invention selects elemental magnesium for pre-magnesium treatment and lithium hydride for pre-lithium treatment is that when other magnesium sources (such as magnesium carbonate, magnesium nitrate, magnesium oxide, etc.) and lithium sources (such as lithium carbonate, lithium nitrate, lithium oxide, etc.) are selected, a large amount of magnesium oxide and lithium oxide that cannot be used for pre-magnesium and pre-lithium treatment will be generated during the preparation process of the pre-magnesium and pre-lithium silicon oxygen negative electrode materials, resulting in a waste of resources. In addition, magnesium oxide and aluminum oxide cannot participate in the charge and discharge reactions in the battery, which is not conducive to improving the capacity retention rate of the silicon oxygen negative electrode material prepared using the pre-magnesium and pre-lithium silicon oxygen negative electrode materials.
[0016] Preferably, the silicon-oxygen material is silicon monoxide.
[0017] The commonly used silicon oxide in the art can be used in the present invention.
[0018] More preferably, the chemical composition formula of silicon dioxide is SiO x , 1≤x<2.
[0019] More preferably, the silicon monoxide is SiO.
[0020] Preferably, the median particle size (D50) of the silicon-oxygen material is 1.5-9.5 μm.
[0021] Preferably, the calcination temperature in the pre-magnesium treatment is 500-1000°C.
[0022] More preferably, the calcination temperature in the pre-magnesium treatment is 600-950°C.
[0023] In the present invention, if the calcination temperature in the pre-magnesium treatment is too low, the elemental magnesium is not likely to fully participate in the pre-magnesium treatment, and the rigidity and structural stability of the silicon-oxygen negative electrode material prepared by the pre-magnesium pre-lithium silicon-oxygen negative electrode material cannot be better increased, and the silicon-oxygen negative electrode material cannot be better inhibited from being heated in the Li + Volume expansion occurs during the process of deintercalation / insertion, and ultimately the capacity retention rate of the silicon oxide negative electrode material cannot be better improved; moreover, at this time, elemental magnesium cannot react with the silicon oxide material to generate more magnesium silicate (MgSiO3), and cannot better improve the initial charge and discharge efficiency of the battery in the battery's charge and discharge reaction, nor can it better prevent the battery's charge and discharge capacity from dropping significantly during multiple cycles, thereby failing to better improve the capacity retention rate of the silicon oxide negative electrode material prepared using the pre-magnesium and pre-lithium silicon oxide negative electrode material.
[0024] If the calcination temperature in the pre-magnesium treatment is too high, elemental magnesium will easily react with the silicon oxide material to generate more other types of impurity silicates, such as Mg2SiO4, etc., which will easily consume lithium continuously during the battery cycle and cannot be precipitated, resulting in the battery's charge and discharge efficiency being unable to be better improved, and the charge and discharge capacity being unable to be better maintained, affecting the life of the silicon oxide negative electrode material, and ultimately unable to better improve the capacity retention rate of the silicon oxide negative electrode material prepared using the pre-magnesium and pre-lithium silicon oxide negative electrode material.
[0025] Preferably, the calcination time in the pre-magnesium treatment is 0.5-4h.
[0026] Preferably, the pre-magnesium treatment is performed under an inert gas atmosphere.
[0027] More preferably, the inert gas is at least one of nitrogen, helium, neon and argon.
[0028] Preferably, the calcination temperature in the pre-lithium treatment is 300-1000°C.
[0029] More preferably, the calcination temperature in the pre-lithium treatment is 500-850°C.
[0030] In the present invention, if the calcination temperature in the pre-lithium treatment is too low, lithium hydride may not be able to participate in the pre-lithium treatment, and the rigidity and structural stability of the silicon oxygen negative electrode material prepared by the pre-magnesium pre-lithium silicon oxygen negative electrode material cannot be better increased, and the silicon oxygen negative electrode material cannot be better inhibited from being heated in the Li + Volume expansion occurs during the process of deintercalation / insertion, and ultimately the capacity retention rate of the silicon oxygen negative electrode material prepared using the pre-magnesium and pre-lithium silicon oxygen negative electrode material cannot be better improved; moreover, at this time, lithium hydride cannot react with the silicon oxygen material to generate more lithium silicate (Li2SiO3), and the initial charge and discharge efficiency of the battery cannot be better improved in the battery's charge and discharge reaction, nor can the battery's charge and discharge capacity be prevented from dropping significantly during multiple cycles, thereby failing to better improve the capacity retention rate of the silicon oxygen negative electrode material prepared using the pre-magnesium and pre-lithium silicon oxygen negative electrode material.
[0031] If the calcination temperature in the pre-lithium treatment is too high, lithium hydride will easily react with the silicon oxide material to generate more other types of impurity silicates, such as Li4SiO4, etc., which will easily consume lithium continuously during the battery cycle and cannot be precipitated, resulting in the battery's charge and discharge efficiency being unable to be better improved, and the charge and discharge capacity being unable to be better maintained, affecting the life of the silicon oxide negative electrode material, and ultimately unable to better improve the capacity retention rate of the silicon oxide negative electrode material prepared using the pre-magnesium and pre-lithium silicon oxide negative electrode material.
[0032] Preferably, the calcination time in the pre-lithium treatment is 0.5-6h.
[0033] Preferably, the pre-lithium treatment is performed under an inert gas atmosphere.
[0034] More preferably, the inert gas is at least one of nitrogen, helium, neon and argon.
[0035] In a second aspect, the present invention provides a pre-magnesium pre-lithium silicon oxide negative electrode material, which is prepared by the preparation method described in the first aspect.
[0036] In a third aspect, the present invention provides an application of a pre-magnesium and pre-lithium silicon-oxygen negative electrode material in a silicon-oxygen negative electrode material.
[0037] In a fourth aspect, the present invention provides a method for preparing a silicon-oxygen negative electrode material, the preparation method comprising the following steps:
[0038] The pre-magnesium and pre-lithium silicon-oxygen negative electrode material is carbon-coated by using carbon source gas and inert gas through chemical vapor deposition to obtain the silicon-oxygen negative electrode material.
[0039] Preferably, the carbon source gas is a hydrocarbon.
[0040] More preferably, the hydrocarbon is at least one of acetylene, methane, propane and cyclohexane.
[0041] Preferably, the carbon coating is carried out at a temperature of 500-800° C. and for a time of 1-4 hours.
[0042] Preferably, the flow rate ratio of the carbon source gas to the inert gas is (0.1-0.5):1.
[0043] Preferably, the inert gas is at least one of nitrogen, helium, neon and argon.
[0044] In a fifth aspect, the present invention provides a silicon-oxygen negative electrode material prepared by the preparation method described in the fourth aspect.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] The method for preparing the pre-magnesium pre-lithium silicon-oxygen negative electrode material of the present invention can increase the rigidity and structural stability of the silicon-oxygen negative electrode material prepared by using the pre-magnesium pre-lithium silicon-oxygen negative electrode material, and inhibit the silicon-oxygen negative electrode material from being heated in the presence of Li + Volume expansion occurs during the process of deintercalation / insertion, which reduces or prevents the reconstruction or detachment of active substances and solid electrolyte interface membrane (SEI) from the silicon-oxygen negative electrode material, maintains the electrode structure, and improves the capacity retention rate of the silicon-oxygen negative electrode material. In addition, elemental magnesium and lithium hydride will also react with silicon-oxygen materials to form magnesium silicate (MgSiO3) and lithium silicate (Li2SiO3), thereby participating in the battery's charge and discharge reaction, improving the battery's initial charge and discharge efficiency, and preventing the battery's charge and discharge capacity from dropping significantly in multiple cycles, thereby improving the capacity retention rate of the silicon-oxygen negative electrode material.
[0047] The reason why the present invention selects elemental magnesium for pre-magnesium treatment and lithium hydride for pre-lithium treatment is that when other magnesium sources (such as magnesium carbonate, magnesium nitrate, magnesium oxide, etc.) and lithium sources (such as lithium carbonate, lithium nitrate, lithium oxide, etc.) are selected, a large amount of magnesium oxide and aluminum oxide that cannot be used for pre-magnesium and pre-lithium treatment will be generated during the preparation process of the pre-magnesium and pre-lithium silicon oxygen negative electrode materials, resulting in a waste of resources. In addition, magnesium oxide and aluminum oxide cannot participate in the charge and discharge reactions in the battery, which is not conducive to improving the capacity retention rate of the silicon oxygen negative electrode material prepared using the pre-magnesium and pre-lithium silicon oxygen negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is the SEM image of the silicon-oxygen negative electrode material of Application Example 1. DETAILED DESCRIPTION
[0049] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0050] The experimental methods without specific conditions in the following examples, comparative examples, application examples and comparative application examples are generally carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.
[0051] In each embodiment and comparative example of the present invention, the use of reagents is as follows:
[0052] The silicon oxide material is SiO, which is commercially available.
[0053] Example 1
[0054] This embodiment provides a pre-magnesium pre-lithium silicon oxide negative electrode material, and the preparation method thereof comprises the following steps:
[0055] A1. Pre-magnesium treatment: 100 g of silicon oxide material and 5 g of magnesium powder (elemental magnesium) were added to a mortar, ground and mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 900 ° C for 3 h to obtain a pre-magnesium silicon oxide material;
[0056] A2 pre-lithium treatment: Add the pre-magnesium silicon oxide material obtained in step A1 and 3g of lithium hydride in a mortar, grind and mix, place in a tube furnace, introduce nitrogen, and calcine at 800 ° C for 6h to obtain a pre-magnesium pre-lithium silicon oxide negative electrode material;
[0057] The mass ratio of the silicon oxide material to magnesium powder (elemental magnesium) is 10:0.5; the mass ratio of the silicon oxide material to lithium hydride is 10:0.3.
[0058] Examples 2-3 and Comparative Examples 1-2
[0059] Example 2-3 and Comparative Example 1-2 provide different pre-magnesium pre-lithium silicon oxide negative electrode materials, which differ from Example 1 in that the mass ratio of silicon oxide material to magnesium powder (elemental magnesium) is different, and the rest is consistent with Example 1, as shown in the following table:
[0060] Table 1 Mass ratio of silicon oxide material to magnesium powder in Examples 1-3 and Comparative Examples 1-2
[0061]
[0062] Examples 4-5 and Comparative Examples 3-4
[0063] Examples 4-5 and Comparative Examples 3-4 provide different pre-magnesium pre-lithium silicon oxide negative electrode materials, which differ from Example 1 in that the mass ratio of silicon oxide material to lithium hydride is different, and the rest is consistent with Example 1, as shown in the following table:
[0064] Table 2 Mass ratio of silicon oxide material to lithium hydride in Examples 1, 4-5 and Comparative Examples 3-4
[0065]
[0066] Embodiment 6-9
[0067] Examples 6-9 provide different pre-magnesium pre-lithium silicon oxide negative electrode materials, which differ from Example 1 in that the calcination temperature in the pre-magnesium treatment is different, and the rest is consistent with Example 1, as shown in the following table:
[0068] Table 3 Calcination temperature in pre-magnesium treatment of Examples 1, 6-9
[0069] Calcination temperature in pre-magnesium treatment / ℃ Example 1 900 Example 6 600 Example 7 950 Example 8 1000 Example 9 500
[0070] Examples 10-13
[0071] Examples 10-13 provide different pre-magnesium pre-lithium silicon oxide negative electrode materials, which differ from Example 1 in that the calcination temperature in the pre-lithium treatment is different, and the rest is consistent with Example 1, as shown in the following table:
[0072] Table 4 Calcination temperature in pre-lithium treatment of Examples 1, 10-13
[0073] Calcination temperature in pre-lithium treatment / ℃ Example 1 800 Example 10 500 Embodiment 11 850 Example 12 1000 Embodiment 13 300
[0074] Embodiment 14
[0075] This embodiment provides a pre-magnesium pre-lithium silicon oxide negative electrode material, and the preparation method thereof comprises the following steps:
[0076] B1. Pre-lithium treatment: 100 g of silicon-oxygen material and 3 g of lithium hydride were added to a mortar, ground and mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 800 ° C for 6 h to obtain a pre-lithium silicon-oxygen material;
[0077] B2. Pre-magnesium treatment: Add the pre-lithium silicon-oxygen material obtained in step B1 and 5 g of magnesium powder (elemental magnesium) into a mortar, grind and mix, place in a tube furnace, introduce nitrogen, and calcine at 900 ° C for 3 h to obtain a pre-magnesium pre-lithium silicon-oxygen negative electrode material;
[0078] The mass ratio of the silicon oxide material to magnesium powder (elemental magnesium) is 10:0.5; the mass ratio of the silicon oxide material to lithium hydride is 10:0.3.
[0079] Examples 15-16 and Comparative Example 5
[0080] Examples 15-16 and Comparative Example 5 provide different pre-magnesium pre-lithium silicon oxide negative electrode materials, which differ from Example 14 in that the mass ratio of silicon oxide material to magnesium powder (elemental magnesium) is different, and the rest is consistent with Example 14, as shown in the following table:
[0081] Table 5 Mass ratio of silicon oxide material to magnesium powder in Examples 14-16 and Comparative Example 5
[0082]
[0083] Comparative Example 6
[0084] This comparative example provides a pre-magnesium pre-lithium silicon oxide negative electrode material, which differs from Example 1 in that 8.3 g (0.206 mol) of magnesium oxide is used instead of 5 g (0.206 mol) of magnesium powder, and 11.28 g (0.377 mol) of lithium oxide is used instead of 3 g (0.377 mol) of lithium hydride, and the rest is consistent with Example 1.
[0085] Comparative Example 7
[0086] This comparative example provides a pre-magnesium pre-lithium silicon oxide negative electrode material, which differs from Example 1 in that 17.38 g (0.206 mol) of magnesium carbonate is used instead of 5 g (0.206 mol) of magnesium powder, and 27.86 g (0.377 mol) of lithium carbonate is used instead of 3 g (0.377 mol) of lithium hydride, and the rest is consistent with Example 1.
[0087] Comparative Example 8
[0088] This comparative example provides a pre-magnesium pre-lithium silicon oxide negative electrode material, and the preparation method thereof comprises the following steps:
[0089] Add 100g of silicon-oxygen material, 5g of magnesium powder (elemental magnesium), and 3g of lithium hydride into a mortar, grind and mix, place in a tube furnace, introduce nitrogen, calcine at 900°C for 6h, and sieve through a 400-mesh sieve to obtain a pre-magnesium pre-lithium silicon-oxygen negative electrode material;
[0090] The mass ratio of the silicon oxide material to magnesium powder (elemental magnesium) is 10:0.5; the mass ratio of the silicon oxide material to lithium hydride is 10:0.3.
[0091] Application examples and comparative application examples
[0092] Application Example 1
[0093] This application example provides a silicon-oxygen negative electrode material, and its SEM image is as follows Figure 1 As shown, the preparation method thereof comprises the following steps:
[0094] Add 80g of the pre-magnesium and pre-lithium silicon oxide negative electrode material prepared in Example 1 into the fluidized bed, introduce nitrogen at a flow rate of 10L / min for replacement, exhaust the air, raise the temperature to 750°C, introduce acetylene at a flow rate of 2L / min and nitrogen at a flow rate of 10L / min, and maintain for 2h to achieve carbon coating of the pre-magnesium and pre-lithium silicon oxide negative electrode material prepared in Example 1 by chemical vapor deposition, so as to obtain the silicon oxide negative electrode material.
[0095] Application Example 2-16 and Comparative Application Example 1-8
[0096] Application Examples 2-16 and Comparative Application Examples 1-8 provide different silicon oxide negative electrode materials. The difference between them and Application Example 1 is that Application Examples 2-16 and Comparative Application Examples 1-8 use the pre-magnesium and pre-lithium silicon oxide negative electrode materials of Examples 2-16 and Comparative Examples 1-8 respectively instead of the pre-magnesium and pre-lithium silicon oxide negative electrode materials of Example 1, and the rest are consistent with Application Example 1.
[0097] Performance Testing
[0098] The performance tests of the silicon-oxygen negative electrode materials of each application example and comparative application example are as follows:
[0099] (1) Preparation of button-type lithium-ion batteries
[0100] A1. Put the silicon-oxygen negative electrode material and the conductive agent (acetylene black) of each application example or comparative application example into an oven, bake at 120°C for 4 hours, and then cool in a drying container; then, weigh the silicon-oxygen negative electrode material and the conductive agent (acetylene black) in a corresponding proportion according to the mass ratio of silicon-oxygen negative electrode material, binder (polyvinylidene fluoride), and conductive agent (acetylene black) of 80:10:10, add them into a 50mL small beaker, and then add the binder solution (5% N-methylpyrrolidone solution of polyvinylidene fluoride by mass fraction), and stir with a stirrer to form a paste;
[0101] A2. Apply the paste evenly on the copper foil to obtain a single-sided surface density of 60g / m 2 The negative electrode sheet was then placed in a blast drying oven and dried at 120°C for 2 hours and pressed (the pressing density of the negative electrode sheet was 2.0 g / cm 3 ), cut into a circular negative electrode sheet with a diameter of 12 mm;
[0102] A3. In an argon atmosphere glove box, a button-type lithium-ion battery was assembled with a circular negative electrode sheet as the negative electrode, a lithium sheet as the positive electrode, and a 1 mol / L LiPF6 ethylene carbonate solution and ethyl methyl carbonate (EMC) in a volume ratio of 3:7 as the electrolyte;
[0103] (2) Measurement of first charge capacity, first coulomb efficiency, and 30-cycle capacity retention rate
[0104] At 25°C and 25% humidity, the button-type lithium-ion battery was charged and discharged using a blue battery test system to measure the first charge capacity (first charge capacity) and first coulomb efficiency of the button-type lithium-ion battery prepared using the silicon-oxygen negative electrode material of each application example or comparative application example; charging and discharging once each was considered as one cycle, and the cycle was performed for 30 cycles, and the charge and discharge capacity of each cycle was recorded, and the 30-cycle capacity retention rate (%) = (first charge capacity - charge capacity of the 30th cycle) / first charge capacity × 100%;
[0105] The present invention uses the size of the 30-cycle capacity retention rate to indicate the size of the capacity retention rate of the silicon-oxygen negative electrode material. The larger the 30-cycle capacity retention rate is, the larger the capacity retention rate of the silicon-oxygen negative electrode material is.
[0106] (3) Observation of slurry gas production
[0107] The silicon-oxygen negative electrode material and the conductive agent (acetylene black) of each application example or comparative application example are placed in an oven, baked at 120° C. for 4 hours, and then transferred to a drying container for cooling; then, the silicon-oxygen negative electrode material and the conductive agent (acetylene black) of the corresponding proportion are weighed according to the mass ratio of silicon-oxygen negative electrode material, binder (polyvinylidene fluoride), and conductive agent (acetylene black) of 80:10:10, and added to a 50 mL small beaker, and then the binder solution (5% N-methylpyrrolidone solution of polyvinylidene fluoride by mass fraction) is added, and the agitator is stirred into a paste as a slurry, and then allowed to stand for 12 hours to observe whether the paste generates bubbles. If bubbles are generated, it means that the slurry produces gas, and if bubbles are not generated, it means that the slurry does not produce gas;
[0108] It is worth noting that if the silicon-oxygen negative electrode material produces gas in the slurry, it means that the first charge capacity and first coulomb efficiency of the battery prepared using the silicon-oxygen negative electrode material are low, and the bonding effect of the binder in the slurry is destroyed, affecting the cycle life of the battery;
[0109] The experimental results are as follows:
[0110] Table 6 Performance test results of silicon-oxygen negative electrode materials in various application examples and comparative application examples
[0111]
[0112]
[0113] As can be seen from Table 6, the preparation method of the pre-magnesium pre-lithium silicon oxygen negative electrode material of the present invention can increase the rigidity and structural stability of the silicon oxygen negative electrode material prepared by using the pre-magnesium pre-lithium silicon oxygen negative electrode material, and inhibit the silicon oxygen negative electrode material from being heated in the Li +Volume expansion occurs during the process of deintercalation / insertion, which reduces or prevents the reconstruction or detachment of active substances and solid electrolyte interface membrane (SEI) from the silicon-oxygen negative electrode material, maintains the electrode structure, and improves the capacity retention rate of the silicon-oxygen negative electrode material. In addition, elemental magnesium and lithium hydride will also react with silicon-oxygen materials to form magnesium silicate (MgSiO3) and lithium silicate (Li2SiO3), thereby participating in the battery's charge and discharge reaction, improving the battery's initial charge and discharge efficiency, and preventing the battery's charge and discharge capacity from dropping significantly in multiple cycles, thereby improving the capacity retention rate of the silicon-oxygen negative electrode material.
[0114] Specifically, it can be seen from Application Examples 1-5 and Comparative Application Examples 1-4 that in the present invention, if the mass ratio of silicon oxide material to elemental magnesium and the mass ratio of silicon oxide material to lithium hydride are too low (i.e., the amount of elemental magnesium and lithium hydride is too much), magnesium and lithium will participate in the formation of more other types of impurity silicates, such as Mg2SiO4 and Li4SiO4, etc., which will continuously consume lithium during the battery cycle and cannot be precipitated, resulting in the inability to improve the charge and discharge efficiency of the battery, and the continuous decrease in the charge and discharge capacity, which affects the life of the silicon oxide negative electrode material and greatly reduces the capacity retention rate of the silicon oxide negative electrode material prepared using the pre-magnesium pre-lithium silicon oxide negative electrode material; if it is too high (i.e., the amount of elemental magnesium and lithium hydride is too low), it is impossible to effectively increase the rigidity and structural stability of the silicon oxide negative electrode material prepared using the pre-magnesium pre-lithium silicon oxide negative electrode material, and it is impossible to inhibit the silicon oxide negative electrode material from being in the Li + Volume expansion occurs during the deintercalation / insertion process, which ultimately leads to a significant decrease in the capacity retention rate of the silicon-oxygen negative electrode material.
[0115] It can be seen from Application Example 1 and Comparative Application Examples 6-7 that the reason why the present invention selects elemental magnesium for pre-magnesium treatment and lithium hydride for pre-lithium treatment is that when other magnesium sources (such as magnesium carbonate, magnesium nitrate, magnesium oxide, etc.) and lithium sources (such as lithium carbonate, lithium nitrate, lithium oxide, etc.) are selected, a large amount of magnesium oxide and aluminum oxide that cannot be used for pre-magnesium and pre-lithium treatment will be generated during the preparation process of the pre-magnesium and pre-lithium silicon oxygen negative electrode materials, resulting in a waste of resources. Moreover, magnesium oxide and aluminum oxide cannot participate in the charge and discharge reactions in the battery, which is not conducive to improving the capacity retention rate of the silicon oxygen negative electrode material prepared using the pre-magnesium and pre-lithium silicon oxygen negative electrode material.
[0116] It can be seen from Application Examples 1, 6-9 that in the present invention, if the calcination temperature in the pre-magnesium treatment is too low, the elemental magnesium is likely to not be able to fully participate in the pre-magnesium treatment, and the rigidity and structural stability of the silicon oxygen negative electrode material prepared by the pre-magnesium pre-lithium silicon oxygen negative electrode material cannot be better increased, and the silicon oxygen negative electrode material cannot be better inhibited from being heated in the Li +Volume expansion occurs during the process of deintercalation / insertion, and ultimately the capacity retention rate of the silicon-oxygen negative electrode material cannot be better improved; moreover, at this time, elemental magnesium cannot react with the silicon-oxygen material to generate more magnesium silicate (MgSiO3), and cannot better improve the initial charge and discharge efficiency of the battery in the charge and discharge reaction of the battery, nor can it better prevent the battery charge and discharge capacity from decreasing significantly in multiple cycles, and thus cannot better improve the capacity retention rate of the silicon-oxygen negative electrode material prepared using the pre-magnesium pre-lithium silicon-oxygen negative electrode material. If the calcination temperature in the pre-magnesium treatment is too high, elemental magnesium is likely to react with the silicon-oxygen material to generate more other types of impurity silicates, such as Mg2SiO4, etc., which are likely to continuously eat lithium during the battery cycle and cannot be precipitated, resulting in the battery's charge and discharge efficiency cannot be better improved, the charge and discharge capacity cannot be better maintained, and the life of the silicon-oxygen negative electrode material cannot be better improved. The capacity retention rate of the silicon-oxygen negative electrode material prepared using the pre-magnesium pre-lithium silicon-oxygen negative electrode material cannot be better improved.
[0117] It can be seen from Application Examples 1 and 10-13 that in the present invention, if the calcination temperature in the pre-lithium treatment is too low, lithium hydride may not be able to fully participate in the pre-lithium treatment, and the rigidity and structural stability of the silicon oxygen negative electrode material prepared by using the pre-magnesium pre-lithium silicon oxygen negative electrode material cannot be better increased, and the silicon oxygen negative electrode material cannot be better inhibited from being heated in the Li + Volume expansion occurs during the process of deintercalation / insertion, and ultimately the capacity retention rate of the silicon oxygen negative electrode material prepared using the pre-magnesium pre-lithium silicon oxygen negative electrode material cannot be better improved; moreover, at this time, lithium hydride cannot react with the silicon oxygen material to generate more lithium silicate (Li2SiO3), and cannot better improve the initial charge and discharge efficiency of the battery in the charge and discharge reaction of the battery, nor can it better prevent the battery charge and discharge capacity from decreasing significantly in multiple cycles, and thus cannot better improve the capacity retention rate of the silicon oxygen negative electrode material prepared using the pre-magnesium pre-lithium silicon oxygen negative electrode material. If the calcination temperature in the pre-lithium treatment is too high, lithium hydride is easy to react with the silicon oxygen material to generate more other types of impurity silicates, such as Li4SiO4, etc., which are easy to continuously eat lithium during the battery cycle and cannot be precipitated, resulting in the battery charge and discharge efficiency cannot be better improved, the charge and discharge capacity cannot be better maintained, affecting the life of the silicon oxygen negative electrode material, and ultimately cannot better improve the capacity retention rate of the silicon oxygen negative electrode material prepared using the pre-magnesium pre-lithium silicon oxygen negative electrode material.
[0118] It can be seen from Application Examples 1-3, Application Examples 14-15 and Comparative Application Example 8 that, in the present invention, whether the silicon oxide material is first subjected to pre-magnesium treatment and then to pre-lithium treatment, or first subjected to pre-lithium treatment and then to pre-magnesium treatment, the capacity retention rate of the silicon oxide negative electrode material prepared using the pre-magnesium and pre-lithium silicon oxide negative electrode material is not much different, but the silicon oxide material cannot be subjected to pre-magnesium treatment and pre-lithium treatment at the same time.
[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a pre-magnesium pre-lithium silicon oxide negative electrode material, characterized in that: The preparation method comprises the following steps: A1. Pre-magnesium treatment: mixing silicon-oxygen material with elemental magnesium, calcining, and obtaining a pre-magnesium silicon-oxygen material; A2. Pre-lithium treatment: Mix the pre-magnesium silicon oxide material with lithium hydride and calcine to obtain the pre-magnesium pre-lithium silicon oxide negative electrode material; and / or B1. Pre-lithium treatment: mixing silicon oxygen material with lithium hydride, calcining to obtain a pre-lithium silicon oxygen material; B2. Pre-magnesium treatment: mixing the pre-lithium silicon-oxygen material with elemental magnesium and calcining to obtain the pre-magnesium pre-lithium silicon-oxygen negative electrode material; Wherein, the mass ratio of the silicon oxide material to elemental magnesium is 10:(0.2-1); the mass ratio of the silicon oxide material to lithium hydride is 10:(0.1-0.8).
2. The method for preparing the pre-magnesium pre-lithium silicon oxide negative electrode material according to claim 1, characterized in that: The calcination temperature in the pre-magnesium treatment is 600-950°C.
3. The method for preparing the pre-magnesium pre-lithium silicon oxide negative electrode material according to claim 1, characterized in that: The calcination temperature in the pre-lithium treatment is 500-850°C.
4. The method for preparing the pre-magnesium pre-lithium silicon oxide negative electrode material according to claim 1, characterized in that: The calcination time in the pre-magnesium treatment is 0.5-4h.
5. The method for preparing the pre-magnesium pre-lithium silicon oxide negative electrode material according to claim 1, characterized in that: The calcination time in the pre-lithium treatment is 0.5-6h.
6. The method for preparing the pre-magnesium pre-lithium silicon oxide negative electrode material according to claim 1, characterized in that: The silicon oxide material is silicon monoxide.
7. A pre-magnesium pre-lithium silicon oxide negative electrode material, characterized in that: The preparation is obtained by the preparation method as claimed in claim 1.
8. Use of the pre-magnesium and pre-lithium silicon-oxygen negative electrode material according to claim 7 in silicon-oxygen negative electrode materials.
9. A method for preparing a silicon-oxygen negative electrode material, characterized in that: The preparation method comprises the following steps: The pre-magnesium pre-lithium silicon-oxygen negative electrode material of claim 7 is carbon-coated using a carbon source gas and an inert gas through chemical vapor deposition to obtain a silicon-oxygen negative electrode material.
10. A silicon-oxygen negative electrode material, characterized in that: The preparation is obtained by the preparation method as claimed in claim 9.
Citation Information
Patent Citations
Ternary doped silicon-based composite material as well as preparation method and application thereof
CN111048770A
Negative electrode material containing metal-doped silicon-based composite material, preparation method and lithium battery
CN111554909A
Negative electrode material, and electrochemical device and electronic device comprising same
CN114530604A
High-first-effect silicon-based negative electrode material and preparation method and application thereof
CN116435494A
Negative active material containing doped metal elements as well as preparation method and application of negative active material
CN117059756A